Modèle de population pour la planification de l’offre de service - Haurie, Alain (L'Actualité économique, 1978)
This paper deals with the problem of adjusting the supply of public services to the demand for such services. In this matter, the planner is faced with a population having a stochastic behavior and he has to solve ticklish resource allocation problems. After presenting a general frame of modeling that fits such problems, the author gives some examples taken from education, social and care services. The last section is devoted to statistical and mathematical problems that have to be solved in order to operationalise such an approach.